Synthesis of an intensive blue pigment with low cobalt content. Issue 4 (March 2018) - Wen, Wei; Yao, Jin-Cheng; Luo, Yu; Lai, Lu-Lu; Wu, Jin-Ming
Abstract: A new blue Co-based inorganic-organic hybrid pigment was fabricated through a rapid one-step synthetic route. The blue pigment was characterized by field-emision scanning electron microscopy, transmittance electron microscopy, X-ray photoelectron spectroscopy, CNH elemental analysis, mercury porosimetry, thermogravimetric analysis, inductively coupled plasma mass spectrometry, and L*a*b* system. The pigment has a foam-like microstructure and its apparent (skeletal) density is 1.4 g/cm 3 . The mass fraction of Co in the pigment is as low as 7.5%. The pigment shows brilliant blue color and its L*, a*, and b* values are 47.5, 20.1, and −41.6, respectively. Moreover, the L*, a*, and b* values can be adjusted simply by changing the composition of the pigments.